When the music's over : an Inspector Banks novel - Robinson, Peter, 1950- (Robinson, Peter, 1950- Inspector Banks series., 2016)
"Two women. Two crimes. The first is a poet claiming she was assaulted decades earlier by a man now regarded as one of the country's national treasures. And the second is a girl found on a remote roadside, her body broken, her life snuffed out. For Alan Banks, newly promoted to Detective Superintendent, the first case rips a tunnel into long-ago days of innocence and discovery, of music and light. And in the victim, he sees an opportunity for magic recaptured ... if he can bring her assailant to justice. For Detective Inspector Annie Banks, the lifeless young woman poses a baffling mystery -- a mystery that will lead her into the unlikeliest of places, interviewing the unlikeliest of suspects."--